PENGARUH PELATIHAN DAN KOMPETENSI TERHADAP KINERJA KARYAWAN - Ginting, Kristi Endah Ndilosa (JEBIM Prima, 2019)
Abstract: Human resources become spotlight as well as foundation for the organization in order to survive in today’s era of globalization. This has to be supported by good training in order to improve the performance of employees that need to be strengthened by competency. The purpose of this study is to determine how much Training influences Performance while being moderated by Competency at the office of Ministry of Commerce Directorate of Metrology Regional I Medan. The methods used in this research are descriptive method and verification method. Analysis tools used are descriptive statistics, regression analysis, validity test, reliability terst and pure moderator. Research results descriptively show that Training, Competency and Performance of Employees at the Ministry of Trade Metrology Directorate Region I are in good condition. Simultaneously, results show that Training had no significant effect on the Performance of employees while being moderated by Competency of employees.